Child Justice System in ‘Uqubat Dropping of Child Sexual Abuse of Children: (Case Study of Meulaboh Syar’iyah Court Decision Number 1/JN.Anak/2022/MS.Mbo) - Fachruddin; Khalid; Yadi Harahap (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2023)
Settlement of criminal cases against children who conflict with the law must be oriented towards the principle of "The Best Interests Of The Child," namely the child's best interests. The Law on the Juvenile Criminal Justice System exists as an embodiment of this principle, prioritizing Restorative Justice to create an agreement on the settlement of criminal cases. With its regional autonomy, Aceh Province has the independence to make its own rules in the form of Qanuns, including Qanuns to resolve criminal cases committed by children, one of which is Qanun number 6 of 2014 concerning Jinayah Law. However, there was disharmony between the Juvenile Criminal Justice System Law and the Jinayah Law Qanun in the trial process and the type of verdict handed down. As in the criminal case of sexual abuse committed by a child, In the Jinayah Law Qanun, there is a separate procedure for determining a sentence for a juvenile offender, which is different from the sentence handed down when referring to the Law on the Juvenile Criminal Justice System. Another example is that diversion is not recognized in the Qanun Jinayah Law, and it becomes an obligation when referring to the Juvenile Criminal Justice System Law. This contradiction also affects the quality of the decisions issued by judges, in this case, the judges of the Syar'iyah Court.